Flora of the Regional Landscape Park “Lysa Gora”: a preliminary analysis and management approaches - Parnikoza, Ivan; Grechyshkina, Yuliia (Biodiversity: Research and Conservation, 2008)
The Regional Landscape Park (RLP) “Lysa Gora” is located in the southeastern part of the city of Kyiv, at the border of the forest and forest-steppe physiographic and vegetation zones. During 100 years, “Lysa Gora” was a restricted-access military zone, which in fact saved its unique biodiversity. The native flora of the RLP “Lysa Gora” consists of at least 352 species of vascular plants belonging to 245 genera and 75 families. In the taxonomical structure the leading roles are played by the families Poaceae (34 species), Asteraceae (32), Fabaceae (26), Rosaceae (20) and Lamiaceae (20). The non-native flora consists of at least 77 species of vascular plants belonging to 63 genera and 29 families (ca. 20% of the total flora). A comprehensive analysis of the native and non-native flora is provided. The stable component of the flora consists of 54 species from 47 genera and 23 families. Epoecophytes (47 species, 61%) greatly prevail. The percentage of archaeophytes (ca. 30%) is lower than that of kenophytes (ca. 70%). Leading roles are played by species native to North America (18, 23%) and the Mediterranean-Central Asian regions (12, 15.5%). Main routes of invasion of non-native species are railway lines coming close to “Lysa Gora” from two sides. Additional hotspots of non-native species are spontaneous garbage dumps. An efficient management system is needed for preventing and restricting further invasions in “Lysa Gora”.